Efektivitas Penerapan Model Pembelajaran Discovery Learning Pada Mata Pelajaran Teknologi Informasi dan Komunikasi di MTsN 4 Bone - Setia Ningsih; Jumadi M Parenreng; Firdaus (EduInovasi: Journal of Basic Educational Studies, 2025)
This quasi-experimental study examined the effectiveness of a treatment using a nonequivalent control group design. One group applied the discovery learning model, while the other acted as a control class with a conventional learning model. The aim was to determine the effectiveness of the discovery learning model for learning information and communication technology in eighth grade at MTsN 4 Bone. Purposive sampling was used to select class VIII C as the experimental group and class VIII B as the control group. The results of the analysis of the three effectiveness indicators are as follows: (1) The average ICT learning achievement score was in the high category, with an 87% increase in student ICT learning achievement. (2) The student activity indicator was met, with an average student activity score of 3.52 in the very active category. (3) The student response questionnaire indicator was met, with 93% of responses being positive. Based on these results, it can be concluded that implementing the discovery learning model is effective for teaching information and communication technology because all criteria were fullfilled